Prevalence of Helminths in Gastrointestinal Tract of Family Murinae from Nakhon Ratchasima, Buri Rum and Surin Provinces - นราพงษ์, ญาณิศา; ภักดีณรงค์, นพคุณ (KKU Science Journal, 2016)
The purpose of this study was to present the prevalence of helminths in gastrointestinal tract of murids from Nakhon Ratchasima, Buri Rum and Surin Provinces. A total of 125 murids during April to October 2014 were collected. 8 species of murids infected with 8 species of helminths (2 cestodes and 6 nematodes). The highest prevalence rate of helminths in murids was 100% in Berylmys berdmorei, 85.7% in Bandicuta savilei, 83.3% in Rattus losea, 68.8% in Bandicuta indica, 54.5% in Rattus exulans, 52.3% in Rattus tanezumi, 42.9% in Mus cervicolor and 28.6% in Mus caroli. The highest prevalence rate of helminths was Hymenolepis diminuta (16.8%), Protospirura siamensis (15.2%), Syphacia muris (14.4), Trichostrongylidae (13.6%), Ptrygodematites sp. (12.8%), Raillietina sp., Syphacia obvelata and Physaloptera sp. (0.8%), respectively. The highest prevalence of helminths was found in Buri Rum (59.0%) followed by Nakhon Ratchasima (58.1%) and Surin (52.4%). Whereas, the highest total helminth species richness was found in Buri Rum provicnce (7 species) followed by in Naknon Rachasima and Surin provinces (4 species each). The results indicated that murids were important vectors of helminth diseases. This data will be benefit to public health for planning control and prevention from helminths in murids to humans and pets.